Gastric dilatation and volvulus (bloat) - A case report and mini review of literature - Kalaiselvan Elangovan; Shivaraju Shivaramu; Swapan K. Maiti; Sunil K.S. Padmanabha; Divya Mohan (Syiah Kuala University, 2021)
Gastric dilatation and volvulus (GDV) is a progressing bloat condition in dogs characterized as dilatation followed by rotation of stomach. A sevenyear old 18 kg black colour female non-descriptive dog presented, with history of difficulty in respiration within half an hour after feeding of curd meals. With the history and general clinical examination the case tentatively diagnosed as gastric dilatation. After unsuccessful advancement of oro-gastric tube, needle gastric paracentesis was performed on left side of the abdomen caudal to the last rib for decompression. Mid-ventral celiotomy and gastrotomy were performed after stabilization of heart rate and respiratory rate. After evacuating the whitish frothy content from the stomach, derotation and incisional gastropexy was performed. On 14thpostoperative day telecommunication confirmed the milk based meal induced GDV canine patient recovered uneventfully. Electrocardiogram monitoring done for first 24 hours period and ventricular arrhythmia was managed by using lidocaine (loading@2mg/ kg bw followed by 25mcg/kg/min for 30 min). It is concluded that on 14th postoperative day telecommunication confirmed the milk based meal induced GDV canine patient recovered uneventfully.